FACTORS RELATED TO DYSMENORRHEA AMONG ADOLESCENTS - Salsabila, Afifah; Hanifah, Laily; Maharani, Fandita Tonyka (IAKMI South Tangerang Branch, 2024)
Background: Dysmenorrhea is a brief pain before or during menstruation that often complain by women. Dysmenorrhea that occurs in adolescents has an impact on decreasing learning activity and concentration thus induced them to absent from school. Method: This cross-sectional study used proportional random sampling of 128 senior high school students. Data collection was conducted using a self-administered questionnaire via Google Forms April - Mei 2022. Data analysis used multiple logistic regression. Results: The proportion of dysmenorrhea is 66.4% and there was a significant relationship between physical activity (POR: 2.42; 95% CI: 1.06 – 5.49), menstrual duration (POR: 3.01; 95% CI: 1.32 – 6.85) and stress (POR: 5.15; 95 % CI: 1.89 – 14.04) with the incidence of dysmenorrhea among adolescents at SMA Negeri 4 Bekasi City with stress as the dominant factor to the incidence of dysmenorrhea, meaning that girls who experienced stress were 5.15 more likely to experienced dysmenorrhea compared to girls who do not experience stress. Conclusion: The factors associated with the occurrence of dysmenorrhea includes physical activity, menstrual duration and stress.